Meeting the Needs of Malaysian Mathematically Talented Students by An Enrichment Program: A Module For Primary School Students - Faieza Samat; Eddie Shahril Ismail (Universitas Muhammadiyah Sidoarjo, 2020)
School holiday enrichment program annually organized by PERMATApintar National Gifted Centre was to uncover hidden talents in science and mathematics. Students in this program were grouped into different courses. In order to run the Introduction to Cryptology course for primary school students, a new module has been developed. This module has been implemented for the first time during the school holiday program in December 2017. Thus, this study aimed at determining mathematics achievement of 34 Malaysian primary school students in Introduction to Cryptology course. An examination consisting of a set of questions on mathematical concepts was being given to each of the students during the final day of the program. Student scores were being evaluated to assess their achievement. Findings indicate that 73.6% of students scored between 80 and 100 in the examination. Students have good achievement in the concept of integers but they have deficiency in the concept of matrices. Hence, it can be concluded that the students indeed have special ability in doing mathematics. Since matrices were new to Malaysian primary school students, thus interesting activities relating to matrices will be included in the module to intensify students’ motivation in mathematics.